Crisis & opportunity : sustainability in American agriculture - Ikerd, John E. (Our sustainable future., 2008)
In Crisis and Opportunity, John E. Ikerd outlines the consequences of agricultural industrialization, then details the methods that can restore economic viability, ecological soundness, and social responsibility to our agricultural system and thus ensure sustainable agriculture as the foundation of a sustainable food system and a sustainable society.